PERKEMBANGAN KAWASAN PERKOTAAN KECIL DI PINGGIRAN KOTA PEKALONGAN - Mardiansjah, Fadjar Hari; Rahayu, Paramita (Jurnal Pendidikan Geografi Gea, 2020)
The growing of peri-urban regions has been characterized urbanization process of cities in Java including in both large and much smaller ones. This paper uses villages’ monograph data from 1990 to 2017 to present the extent to which peri-urban development has been occurring in Pekalongan region, as an elaboration of such process in a small city in Java, the densest populated big islands in the world. The study reveals peri-urban development process also happen in Pekalongan Region that shows as an extended urbanization phenomenon from the core to the surroundings peripheries. The elaboration shows peri-urban development in this region is highly concentrated along the national road of Pantura that form a more than 40 km urban corridor. Long term analysis shows the influence of the regional road network as well as the availability of the previous urban centers in the peripheries of Pekalongan City bring strong support to the extended formation of Pekalongan Urban Region. The paper concludes with a discussion of the policy implications of the findings.